Percutaneous endoscopic gastrostomy for refractory epilepsy and medication refusal. Issue 7 (4th March 2019) - Howard, Caoimhe; Macken, William L; Connolly, Ann; Keegan, Maria; Coghlan, David; Webb, David W
Abstract : Objective: Current guidelines for percutaneous endoscopic gastrostomy (PEG) placement focus largely on maintaining enteral feeding when oral feeding is no longer possible or adequate with an emphasis on nutrition and quality of life (QOL). Previous publications have also alluded to potential benefits in medication adherence, for example, in children with HIV, renal disease and neurodisability. We describe a cohort of children with refractory epilepsy who refused oral medication and in whom PEG tube placement was initiated for the purpose of drug administration. Design: We identified children from the medical records of two tertiary paediatric units over a 9-year period who had PEG tube placement for administration of antiepileptic drug (AED) therapy and collected demographic and clinical details from chart reviews. We assessed parent-reported changes in seizure control and QOL using a structured questionnaire. Results: Ten patients met the inclusion criteria. All families reported an improvement in ease of administering medications and eight reported a significant improvement in QOL. Nine children had a decrease in seizure frequency (lasting more than 12 months) following PEG tube placement, including two who underwent surgical intervention for their epilepsy during that period. Four had either a decrease in the number of drugs administered or their doses and four went on to receive fluids and nutrition through their tube on a regular basis. Seven reported PEG complications, which did not require removal of the PEG. Conclusions: This case series of children with resistant epilepsy demonstrates improvement in seizure control and QOL following PEG tube placement for AED administration.